The Adoption of the Euro, Choice of Currency Regime and Integration of Payment Systems - Michael C. Bonello; George M. von Furstenberg; Kari Kemppainen; Sinikka Salo (SUERF - The European Money and Finance Forum, 2006)
1) The Adoption of the Euro by New Member States: Challenges and Vulnerabilities by Michael C. Bonello 2) The Economics of Offshore Financial Services and the Choice of Tax, Currency, and Exchange-Rate Regimes by George M. von Furstenberg 3) Promoting Integration of European Retail Payment Systems: Role of Competition, Cooperation and Regulation (Kari Kemppainen and Sinikka Salo)
Keywords: F31; F33; F36; F53; G10; G28; L14; 330; Offshore Financial Centers; International Financial Services; Exchange-Rate Regime; Taxation of Nonresidents; Currency Substitution; financial integration; network economics; retail payment systems; Single Euro Payments Area; Eurozone; EU-Mitgliedschaft; Euro; EU-Mitgliedschaft